2018
DOI: 10.1080/20961790.2018.1446721
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse silica nanoparticle suspension for developing latent blood fingermarks

Abstract: Traditional fingermark developing methods are unsuitable for developing and extracting latent blood fingermarks on dark surfaces at crime scene because of their ineffectiveness or tedious operation procedures. In the present work, an effective and simple method was developed to serve this purpose using a suspension of monodisperse silica nanoparticles (MSNs). A suspension of 0.1 g/mL of MSNs was prepared by dispersing MSNs ultrasonically into an ethanol solution containing 1.0% Tween 80 and then uniformly spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…This method utilizes the photonic crystal effect of monodisperse silica nanoparticles to improve latent blood fingermarks kept on black plastic bags surfaces for at least 30 days without the requirement of surfaces to functionalize and conjugate the dye or fluorescently label the molecules. 116 It has been widely known that the biodegradability of conventional silica nanoparticles is limited. Hence, the progression of intrinsically biodegradable SNPs has great attention and has aroused extensive research interest during the last decade, and many strategies have been investigated to enhance the biodegradability.…”
Section: Silica-based Nanomaterials and Its Applicationsmentioning
confidence: 99%
“…This method utilizes the photonic crystal effect of monodisperse silica nanoparticles to improve latent blood fingermarks kept on black plastic bags surfaces for at least 30 days without the requirement of surfaces to functionalize and conjugate the dye or fluorescently label the molecules. 116 It has been widely known that the biodegradability of conventional silica nanoparticles is limited. Hence, the progression of intrinsically biodegradable SNPs has great attention and has aroused extensive research interest during the last decade, and many strategies have been investigated to enhance the biodegradability.…”
Section: Silica-based Nanomaterials and Its Applicationsmentioning
confidence: 99%
“…These; overview photos, photography of evidence, and close-up photos of evidence (see Figs. 1,2,3). In general view shots, the crime scene is shot from different angles.…”
Section: Crime Scene Investigation and Finding Typesmentioning
confidence: 99%
“…There are chemicals used for chemical development. Amido contains chemicals such as Black, Purple acid, protein dyes [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that NPs synthesized with a binary mixture of TEOS and PTEOS, and WA6 fluorophore used as an aqueous suspension on glass substrates gave clear, luminescence ridges with secondary-and tertiary-level details and high contrast. Meng et al used SiO 2 NPs to detect fingermarks in blood on black plastic (Meng et al, 2018). A suspension of the NPs was made by dispersing it in ethanol and surfactant, and it was used to spray on the fingermarks.…”
Section: Silica Nps Used In Solutionmentioning
confidence: 99%